Ketahanan Pangan Rumah Tangga dan Kepatuhan Konsumsi Tablet Tambah Darah dengan Berat Badan Lahir Bayi di Kota Semarang - Ayu Rahadiyanti; Frida Zadani Anintya; Fillah Fithra Dieny; Mursid Tri Susilo; Martha Ardiaria (Poltekkes Kemenkes Yogyakarta, 2026)
Background: Infants with low birth weight (LBW) are one of the causes of high IMR. Infant birth weight is influenced by two factors: household food security and adherence to consumption of blood supplement tablets (TTD). Objective: To determine the relationship between household food security and compliance of TTD consumption by pregnant women with LBW of infants in Semarang City. Methods: This prospective cohort observational study used a sample of 55 pregnant women at the health center in Semarang City who were taken by purposive sampling. Data on food security was collected using HFIAS, TTD consumption compliance using MMAS-8, and LBW through MCH book. Data analysis used Spearman Rho test and logistic regression test. Results: 40% of LBW babies, 32.7% of pregnant women with food insecurity and 56.4% of pregnant women with low TTD consumption compliance. There was no association between household food security and LBW (p=0.142). There was an association between TTD consumption compliance and LBW (p=0.010). Pregnant women with low TTD consumption compliance had a 20.4 times risk of delivering LBW babies compared to pregnant women with high TTD consumption compliance (OR: 20.454 90% CI 2.835,147.5). Conclusion: There is an association between TTD consumption compliance and LBW in Semarang City